18.8k views
5 votes
Answer Is not B
help is appreciated​

Answer Is not B help is appreciated​-example-1
User Brablc
by
5.3k points

2 Answers

6 votes

Answer:

d.

Step-by-step explanation: the other person said it and they seem to be way smarter then i am so pick d

User Shanie
by
5.4k points
4 votes

Answer:

d

Explanation:

The sum to n terms of a geometric sequence is


S_(n) =
(a(r^(n)-1) )/(r-1)

where a is the first term and r the common ratio

Here a = 3 and r = 12 ÷ 3 = 4 , thus


S_(8) =
(3(4^(8)-1) )/(4-1)

=
(3(65536-1))/(3) = 65536 - 1 = 65535 → d

User Carlossless
by
5.3k points